The first time devastating food poisoning happened in Taiwan - Bongkrekic acid poisoning - Yu-Jang Su (Elsevier, 2024)
Bongkrekic acid (BKA), a rarely happened foodborne toxin by Burkholderia gladioli pathovar cocovenenans (Burkholderia cocovenenans) might leads to devastating life-threatening condition after eating meal contaminated BKA. Unbelievable event from March 19, 2024, to March 24, 2024, there was an outbreak of BAP in a luxury shopping area of eastern Taipei, Taiwan. Most of the victims are young to middle-aged people who made a tour over there and ate the cooked wet rice noodles. Of them, 13 males and 20 females, aged 40.9 ± 14.7 years old visited or were sent by ambulances to the emergency department presenting with watery diarrhea, and vomiting. Some progressed to severe hepatic and renal failure, altered mental status, disseminated intravascular coagulation, and fatalities within several hours within 2 days. The primary health workers especially emergency physicians need to keep in mind of BKA poisoning is quite different in presentations from other infectious colitis commonly seen before. Knowing the toxic-kinetic and toxic-dynamic mechanisms is important to farseeing the presentation of these BAP patients. Throughout this outbreak, we gathered abundant experiences in mitigating and managing these debilitated patients. Aggressively supportive care and early liver transplantation if there is no concurrent inflammatory process and the patient's condition is tolerable to surgical intervention saves lives. For food safety education, it is crucial to enhance our understanding of inhibiting BKA production and promote proper food preservation methods and a suitable environment to ensure food safety.